Territorial Governance Local Development, Rural Areas and Agrofood Systems - Torre, André; Traversac, Jean-Baptiste.; SpringerLink (Online service). (Heidelberg Physica-Verlag HD, 2011)
This work aims to present the most recent developments regarding territorial governance, placing particular emphasis on rural and periurban areas. The reader will find information on the processes of development of European regions, as well as on the behaviours and strategies adopted by the different actors who live in these territories and contribute to the latter's livelihood. The first part of the book analyses the structural changes in the modes of production that have affected these territories. The second part addresses the questions of methodology and of the structures of governance of local development in rural areas. The last section makes an assessment of the geographical indications as tools of governance of local agrifood chains. The book was written by economists, geographers, land use planners and specialists of the questions of governance and management of rural and periurban areas.
1 Introduction -- 2 Changing Trends in Rural Self-Employment in Europe and Turkey -- 3 A New Form of Small Industrial Business in Rural Area: To Exceeding the Local Roots? -- 4 The Modalities of Territorial Embeddedness of French Cooperative Groups -- 5 Strategies for Sustainable Regional Development and Conditions for Vital Coalitions in the Netherlands -- 6 Governance, Rural Development and Farmers' Participation in Irish Local Food Movements -- 7 Spatial Analysis for Policy Evaluation of the Rural World: Portuguese Agriculture in the Last Decade -- 8 Governance and Contested Land Use in the Netherlands -- 9 A Brazilian Perspective on Geographical Indications -- 10 Cooperation and Governance in Wine Territories: A new Institutional Economic Analysis -- 11 Under what Conditions Geographical Indications Protection Schemes Can Be Considered as Public Goods for Sustainable Development? -- 12 Conclusion: Rural Territories, Governance and Rural Policies: What Perspectives?.
Electronic reproduction.
Keywords: Economic development -- European Union countries; Regional economics; Agriculture -- Economic aspects -- European Union countries; European Union countries -- Economic conditions -- Regional disparities; Electronic books